The subjectivity of the human being in the process of development and transformation – a historiosophical reflection - Kmieciński, Jerzy (Myths and Stereotypes in the Collective Representations, 2019)
The article deals with one of the most important questions in the history of humanity: why we are here. The author provides a wide overview of the evolution of human thought around the issue of our origins. We continuously have been asking ourselves the same question throughout our history, but it lead us to different conclusions. The essence of life is inseparably linked with the reason of our existence. The effect of which is visible not only in philosophy or sociology, but also in arts. While philosophy tries to describe this essence by thought, art tries to describe it by form and shape. While there is no philosophy without relation to the genesis of humanity, there is no art without emotions. This is why the humans are so curious to discover the past both by thought and form. We simply try to answer this one particular prehistoric question.